Incidence of dry socket after extraction and its associated factors: Experience at BPKIHS (Journal of BP Koirala Institute of Health Sciences, 2025)
Background: Dry socket is one of the most common complications of tooth extraction, and its prevalence may reach up to 35%. Several contributing factors have been reported to be associated with an increased risk of developing dry socket. The objective of this study was to evaluate the incidence of dry socket after extraction and to assess the factor associated with its occurrence.Materials and methods: This study included all patients visiting the Department of Oral and Maxillofacial Surgery, BP Koirala Institute of Health Sciences for routine extraction from December 2016 to June 2017. Information regarding gender, oral hygiene status, type of extraction, operator experience, cause of extraction and associated medical conditions were recorded along with the occurrence of dry socket. Further statistical analysis was conducted to explore the association of these factors with the occurrence of dry socket.Results: During the study period, 2151 teeth were extracted from 1636 patients. Only 68 patients developed dry sockets, giving an incidence of 4% among patient treated and 3.2 % of the teeth extracted. The frequency of dry socket for males and females was 25 (4.4%) and 43 (4.0%) respectively. This difference was found to be statically insignificant (χ2 = 0.18; p = 0.669). There were 13 (19%) cases of dry socket with significant medical conditions and 55 (81%) cases of dry socket with single extractions.Conclusion: There were no significant association of dry socket with gender, oral hygiene, type of extraction and operators.